دراسة خصائص الطيف الغذائي وبعض المؤشرات البيولوجية لسمك السوري Sargocentron rubrum المياه البحرية السورية - غالية, محمد; ابراهيم, أمير (Latakia University Journal -Basic Sciences Series, 2018)
أجري البحث خلال الأعوام 2002-2003م على/435/ فرداً من سمك السوري المصادة من المياه البحرية السورية. تمت دراسة التركيب النوعي والوزني للعناصر الغذائية الداخلة في الطيف الغذائي للسمك السوري، فضلا عن بعض المعاملات البيولوجية (معامل الحالة Condition factor، معامل الامتلاء العام، دليل المصادفة)، والتركيب الطولي والوزني والجنسي للأفراد المدروسة. تبين أن التركيب النوعي للعناصر الغذائية المكونة للطيف الغذائي للسمك السوري، يتألف من أكثر من عشرين عنصراً غذائياً منتمياً إلى أربع مجموعات تصنيفية رئيسية (قشريات، رخويات، حلقيات، أسماك ). احتلت المرتبة الأولى بينها القشريات Cructacea ممثلة بـ(17) نوعاً، وخاصة Decapoda التي تمثلت بـ(13) نوعاُ في الأنبوب الهضمي لسمك السوري، وكان القشري Palaemon elegans أكثر أنواع هذه الرتبة غزارة.واحتلت رتبةIsopoda المرتبة الثانية حيث تمثلت بنوعين. كما شكل صف كثيرات الأهلاب Polychaeta (وخاصة النوع Eulalia viridis) المرتبة الثالثة. تلتها الرخويات Mollusca ممثلة بالنوع Chiton squamosus من رتبة متعددات اللوحة Polyplacophora. وألفت صغار الأسماك المرتبة الرابعة (مثل صغار سمك Gobius sp. وSparisoma credence، وسمك Panturichthys fowleri وغيرها ). كما لوحظ عدم وجود فروق كبيرة في التركيب النوعي للطيف الغذائي للسمك السوري، تبعاُ لتغيرات الطول والجنس للأفراد المدروسة وكذلك بالنسبة إلى قيم المعاملات الأخرى (معامل الحالة، ومعامل الإمتلاء العام). This research was done during the period 2002-2003 on /435/ of Squirrelfish individuals (Sargocentron rubrum), caught in the Syrian Marine waters. The specific and weight structures of food elements in food spectrum of the fish were studied. In addition, some biological factors (condition factor, general fullness factor and frequency of occurrence, length, weight and sex structures of fish) were also analized. It had been revealed that the specific structure of food elements of the Squirrelfish, consists of more than twenty food elements belonging to four major taxonomic groups (Crustacea, Mollusca, Annelida and Fishes). The crustacean was the first among fish to rely on and represented by (17) species, especially Decapods (12 species; especially, the Palaemon elegans). The Isopods was in the second level, where it was represented by two species. The Polychaeta (especially Eulalia viridis) was in the third level followed by the Mollusks (represented by Chiton squamosus from the Polyplacophora). The young fish individuals were in the forth level of food spectrum (represented by Gobius sp, Sparisoma credence and Panturichthys fowleri). There were not any big differences in specific structure of food spectrum with regards to the length or sex differences among the studied fish. Similarly no big differences were observed in regards to other factors such as condition factor or general fullness factor.